Assistive Robotic Technology: A Review - Anton Satria Prabuwono; Khalid Hammed S. Allehaibi; Kurnianingsih Kurnianingsih (Computer Engineering and Applications Journal, 2017)
Older people with chronic conditions even lead to some disabilities face many challenges in performing daily life. Assistive robot is considered as a tool to provide companionship and assist daily life of older people and disabled people. This paper presents a review of assistive robotic technology, particularly for older people and disabled people. The result of this review constitutes a step towards the development of assistive robots capable of helping some problems of older people and disabled people. Hence, they may remain in at home and live independently.